Semiparametric additive indices for binary response and generalized additive models - Wolfgang Härdle; Sylvie Huet; Enno Mammen; Stefan Sperlich (Humboldt University of Berlin, Interdisciplinary Research Project 373: Quantification and Simulation of Economic Processes, 1998)
Models are studied where the response Y and covariates X, T are assumed to fulfill E(Y|X; T) = GXT Ø + » + m1(T1) + … + md(Td). Here G is a known (link) function, Ø is an unknown parameter, and m1, …, md are unknown functions. In particular, we consider additive binary response models where the response Y is binary. In these models, given X and T, the response Y has a Bernoulli distribution with parameter GXT Ø + » + m1(T1) + … + md(Td). The paper discusses estimation of Ø and m1, …, md. Procedures are proposed for testing linearity of the additive components m1, …, md. Furthermore, bootstrap uniform confidence intervals for the additive components are introduced. The practical performance of the proposed methods is discussed in simulations and in two economic applications.
urn:nbn:de:kobv:11-10060660
Keywords: 330